Factors associated with persistent symptoms after COVID-19 infection: a longitudinal study on an Italian cohort of patients discharged from hospital - Carla Amato; Paolo Iovino; Michele Spinicci; Yari Longobucco; Luca Livi; Lorenzo Giovannoni; Cecilia Guidotti; Luca Pietrini; Francesca Braschi; Clara De Filippis; Luca Ermini; Leonardo Gori; et al. (Infectious Diseases, 2026)

Correction: Early detection of hypovolemia by venous pulse wave velocity and vena cava ultrasound imaging - Marco Romanelli; Leonardo Ermini; Piero Policastro; Ruben Allois; Luca Mesin; Paolo Pasquero; Silvestro Roatta (European Journal of Applied Physiology, 2026)

Early detection of hypovolemia by venous pulse wave velocity and vena cava ultrasound imaging - Marco Romanelli; Leonardo Ermini; Piero Policastro; Ruben Allois; Luca Mesin; Paolo Pasquero; Silvestro Roatta (European Journal of Applied Physiology, 2026)
Purpose Non-invasive assessment of the volemic status is still an open and urgent clinical need. The pulse wave velocity in the venous compartment (vPWV) has recently been re-proposed as a possible indicator but still needs to be tested in different settings including hypovolemic conditions. Methods The present study aims at investigating the response of the vPWV to hypovolemic changes of different magnitude, as provided by the lower body negative pressure (LBNP) and using the ultrasound monitoring of the inferior vena cava (IVC) as a reference. In 28 healthy subjects, vPWV was measured at the arm during exposure to short (90 s at -10, -20, -30, -40 mmHg) and long (5 min at -30 mmHg) exposure to LBNP, along with arterial blood pressure (ABP) and heart rate (HR). In a subgroup of 17 subjects IVC was successfully monitored and the full-time course of IVC diameter (dIVC) and collapsibility indices were extracted from the recording. Results While collapsibility indices were little responsive, vPWV and dIVC were significantly affected by LBNP, decreasing by 19.5 ± 9.7 and 20.9 ± 21.3% at -10 mmHg, respectively. Only the respiratory caval index exhibited significant increases at LBNP ≤ 30mmHg. As compared to other variables vPWV exhibited best reproducibilty: coefficient of variation < 5%. Conclusion vPWV appears to be a promising non-invasive indicator of blood volume decrease with early high sensitivity and reproducibilty.

Can improving climate change perception lead to more environmentally friendly choices? Evidence from an immersive virtual environment experiment - Tommaso Luzzati; Stefano Baraldi; Sara Ermini; Claudia Faita; Valeria Faralla; Pietro Guarnieri; Luca Lusuardi; Vincenzo Santalucia; Sara Scipioni; Matteo Sirizzotti; Alessandro Innocenti (Ecological Economics, 2025)

Ancient horse genomes reveal the timing and extent of dispersals across the Bering Land Bridge - Alisa O. Vershinina; Peter D. Heintzman; Duane G. Froese; Grant Zazula; Molly Cassatt‐Johnstone; Love Dalén; Clio Der Sarkissian; Shelby G. Dunn; Luca Ermini; Cristina Gamba; Pamela Groves; Joshua D. Kapp; et al. (Molecular Ecology, 2021)
The Bering Land Bridge (BLB) last connected Eurasia and North America during the Late Pleistocene. Although the BLB would have enabled transfers of terrestrial biota in both directions, it also acted as an ecological filter whose permeability varied considerably over time. Here we explore the possible impacts of this ecological corridor on genetic diversity within, and connectivity among, populations of a once wide‐ranging group, the caballine horses ( Equus spp.). Using a panel of 187 mitochondrial and eight nuclear genomes recovered from present‐day and extinct caballine horses sampled across the Holarctic, we found that Eurasian horse populations initially diverged from those in North America, their ancestral continent, around 1.0–0.8 million years ago. Subsequent to this split our mitochondrial DNA analysis identified two bidirectional long‐range dispersals across the BLB ~875–625 and ~200–50 thousand years ago, during the Middle and Late Pleistocene. Whole genome analysis indicated low levels of gene flow between North American and Eurasian horse populations, which probably occurred as a result of these inferred dispersals. Nonetheless, mitochondrial and nuclear diversity of caballine horse populations retained strong phylogeographical structuring. Our results suggest that barriers to gene flow, currently unidentified but possibly related to habitat distribution across Beringia or ongoing evolutionary divergence, played an important role in shaping the early genetic history of caballine horses, including the ancestors of living horses within Equus ferus .